Penerapan Model Pembelajaran Kooperatif Teams Assisted Individualization (TAI) dalam Pembelajaran Geografi - Kiki, Friskilia; Andaria, Kalvin S.; Sulastriningsih, Sri (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2025)
This study aims to analyze the effect of implementing the Team-Assisted Individualization (TAI) cooperative learning model on the Geography learning outcomes of eleventh-grade students at SMA Negeri 5 Tana Toraja. The TAI model emphasizes learning in small heterogeneous groups, enabling active interaction among students in understanding the learning materials. This research employed a quantitative approach with an experimental method using a pretest–posttest control group design. The research subjects consisted of two classes, namely an experimental class and a control class, each consisting of 32 students. The experimental class received treatment through the implementation of the TAI cooperative learning model, while the control class was taught using conventional learning methods. The data collection techniques included learning outcome tests, observation, and documentation. Data analysis was conducted through normality and homogeneity tests as prerequisites for analysis, as well as comparison of the average scores of students’ learning outcomes. The results of the study indicate that the average learning outcomes of students in the experimental class were higher than those in the control class. These findings show that the implementation of the Team-Assisted Individualization (TAI) cooperative learning model has a positive effect on improving students’ Geography learning outcomes. The TAI model can be used as an alternative and effective learning model to enhance students’ activeness and learning outcomes in Geography learning.